Determinants of sheep and goat meat consumption in Switzerland - Matteo Aepli; Robert Finger (Agricultural and Food Economics, 2013)
In this study, we estimated the influence of different meat prices, socio-demographic and geographic variables on sheep and goat meat demand using the Swiss household expenditure survey from 2000 to 2005, a micro data set on 20,940 households resident in Switzerland. This study is motivated by the fact that sheep and goats play a major economic role especially for small farms in Swiss agriculture and contribute to conservation of landscape and biodiversity especially in the mountain regions. Considering the high share of households with zero consumption for sheep and goat meat, we estimated a Tobit-model. Missing prices are replaced by monthly, regional market prices where possible, or by quality adjusted prices based on unit values. Our results show that pork is a substitute for sheep and goat meat, whereas beef is a complementary good, and that socio-demographic variables like education or the presence of children and geographic variables are important in determining demand of sheep and goat meat.
Keywords: 330; Sheep and goat meat; Consumer demand; Tobit-Model